Antioxidant, anticancer and antimicrobial activities of methanolic extracts from enicosanthellum pulchrum (King) heusden - Noraziah Nordin,; Syam Mohan,; Najihah Mohd. Hashim,; Asdren Zajm,; Noor Shafifiyaz Mohd. Yazid,; Mashitoh Abdul Rahman,; Fatima Abdelmutaal Ahmed Omer,; Hanita Omar,; Fatimah A'fifah Alias,; Hapipah Mohd. Ali, (Universiti Kebangsaan Malaysia, 2014)
Biological activities of crude methanolic extracts from leaves, barks, twigs and roots of Enicosanthellum pulchrum were investigated in four bioassays. The antioxidant, 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging assay showed that bark and twig extracts showed high inhibitory activity with 60 and 56% inhibition at 1 mg/mL and IC50 values of 0.43 ± 0.04 and 0.64 ± 0.05 mg/mL, respectively. The bark and root extracts showed greater reducing power (FRAP) than several standard drugs used in the bioassay. Methanolic extracts of leaves, twigs and roots displayed strong cytotoxicity to breast cancer cell line (MCF-7), myelomonocytic leukaemia cell line (WEHI-3) and ovarian cancer cell line (CAOV-3); the IC50 of the leaf extract were 7.8 ± 0.85 μg/mL (MCF-7) and 9.0 ± 0.13 μg/mL (WEHI-3), while those for the twig and root extracts were 13.9 ± 0.35 and 7.3 ± 0.98 μg/mL (CAOV-3), respectively. In the antimicrobial assays, the extracts were tested against ten bacterial strains and two fungal strains. Bark and twig extracts displayed high inhibitory activity to Bacillus subtilis with 13.3 ± 0.57 and 12.0 ± 0.01 mm inhibition, respectively. In addition, the twig extract displayed better minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) compared with the bark extract (MIC 0.5 and 1.0 mg/mL, MBC 1.0 and 2.0 mg/mL, respectively). For antifungal activity, all extracts showed inhibition on Candida albicans but not on Aspergillus niger. The obtained results suggested that this plant may possibly contain bioactive compounds in the active extracts.